2005
DOI: 10.1248/cpb.53.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poly(ethylene glycol) (PEG) Concentration on the Permeability of PEG-Grafted Liposomes

Abstract: Liposomal drug delivery systems (DDS) have been widely researched for use in drug toxicity reduction and/or drug targeting to desired target tissues.1) However, liposomes are rapidly removed from the circulation following their intravenous administration primarily by Kupffer cells in the liver and fixed macrophages in the spleen. Thus, it is important to develop modified liposomes that are able to avoid uptake by the reticuloendothelial system (RES) and extend their circulation half-life in vivo. Many studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…The effect of PB-PEO on vesicle permeability is reminiscent of the effect that PEG-ylation exerts on the self-assembly and permeability of liposomes [30][31][32][33]. It was observed that addition of increasing concentrations of DSPE-PEG (DSPE: distearoylphosphatidylethanolamine; M W(PEG) > 2000) decreases the CF permeability of the PEG-ylated liposomes [32].…”
Section: Encapsulation Efficiency and Membrane Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of PB-PEO on vesicle permeability is reminiscent of the effect that PEG-ylation exerts on the self-assembly and permeability of liposomes [30][31][32][33]. It was observed that addition of increasing concentrations of DSPE-PEG (DSPE: distearoylphosphatidylethanolamine; M W(PEG) > 2000) decreases the CF permeability of the PEG-ylated liposomes [32].…”
Section: Encapsulation Efficiency and Membrane Permeabilitymentioning
confidence: 99%
“…It was observed that addition of increasing concentrations of DSPE-PEG (DSPE: distearoylphosphatidylethanolamine; M W(PEG) > 2000) decreases the CF permeability of the PEG-ylated liposomes [32]. The PEG-block of the PB-PEO polymer, when introduced into the lipid membrane, could have a similar effect.…”
Section: Encapsulation Efficiency and Membrane Permeabilitymentioning
confidence: 99%
“…The increased circulation halflife of PEG-liposomes has been attributed to the steric repulsive barrier due to the covalently attached PEG around the liposomes. 10,11) We have reported, [12][13][14] the effect of PEG-lipid on the physicochemical properties of liposomes. The addition of PEG-lipid to liposomes caused lateral phase separation, and the fluidity in the interfacial region of the liposomal bilayer membranes was markedly increased.…”
mentioning
confidence: 99%
“…12 Polyethylene glycol (PEG)-lipids can be incorporated into the lipid bilayer to enhance biocompatibility and increase circulation times. 13 This modification is especially effective in passively targeting malignant tissue, with increased liposomal uptake through leaky tumor microvasculature and prolonged retention time due to reduced lymphatic drainage occurring via the enhanced permeability and retention (EPR) effect. 14,15 We have previously demonstrated that peripheral administration of PEGylated nanoparticles containing anticancer Survivin siRNA leads to a significant reduction in tumor growth in a murine xenograft model of breast cancer.…”
mentioning
confidence: 99%